The Dilemma of Islamic Scholars in Responding to the COVID-19 Outbreak in Manado City - Rajafi, Ahmad (Institut Agama Islam Negeri (IAIN) Manado, 2023)
The study explores the evolving perceptions of Muslim communities in Manado City regarding religious scholars, particularly in light of the Indonesian Ulema Council's directives on home worship during the COVID-19 pandemic. Using a social jurisprudence philosophy-based approach, the research aims to discern whether the resistance exhibited signifies normalized behavior or poses a threat to religious existence. Spanning from April to November 2020, the study employed field investigations, including observations, interviews with five key informants, and documentation analysis within an interactive model. The findings highlight a sense of hesitation among Manado's clerical bodies, leading to discord and inconsistencies in societal practices, consequently redirecting followers' attention towards mosque imams. However, interpreting this resistance through a social jurisprudence lens suggests positive developments that may not jeopardize the religious foundations of Manado Muslims. Rather, their defiance could be seen as constructive feedback aimed at reinstating the prominence and authority of scholars among Islamic devotees. This shift in focus should be acknowledged as a means to strengthen the relationship between scholars and their followers within the religious landscape